The Praxis of English Language Teaching and Learning (PELT) Beyond the Binaries: Researching Critically in EFL Classrooms - Vicars, Mark.; Vicars, Mark.; Steinberg, Shirley R.; Steinberg, Shirley R.; McKenna, Tarquam.; McKenna, Tarquam.; Cacciattolo, Marcelle.; Cacciattolo, Marcelle. (Critical New Literacies: The Praxis of English Language Teaching and Learning (PELT), 2015)
This edition of Critical New Literacies: The Praxis of English Language Teaching and Learning (PELT) begins with an examination of bricolage as a way to engage in critical research in TEFL/TESOL teaching and research. The volume considers the quality of ‘encounter’ needed in the global and intercultural classroom. The authors address validity, reliability and an authentic need for research which has at its heart ethical practice. Disenfranchisement of the co-participants in research, which is usually not considered, is reviewed in the volume. The manner in which quantitative methods can be used to deliberate on “praxis” is also explored. Self-reflexive practice is at the heart of EFL research and remains central to this volume. The authors are all praxis based research practitioners and make the work of research accessible, equitable and socially just. This series has at its core the need to state that equitable research is about shared authority and shared power. These nine authors address the periphery and in doing so contest the way the world sees research. The PELT series has a disruptive quality as its raison d’etre and Steinberg et al are asking us to revisit; review and re-assess the notion of our life work as researchers in EAL, ESL, TEFL and TESOL. These nine authors are all global leaders in research inquiry and the provocations offered here are unified in the parading by questioning the more traditional field of research inquiry. The ethic of care and courage is encapsulated in this edition.